2020
DOI: 10.1186/s12940-020-00653-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of life loss per death attributable to ambient temperature among various development regions: a nationwide study in 364 locations in China

Abstract: Background Several studies have investigated the associations between ambient temperature and years of life lost (YLLs), but few focused on the difference of life loss attributable to temperature among different socioeconomic development levels. Objectives We investigated the disparity in temperature-YLL rate relationships and life loss per death attributable to nonoptimal temperature in regions with various development levels. Methods Three hundred sixty-four Chinese counties or districts were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Previous studies had generally found that the death burden caused by low temperatures was higher than that of high temperatures ( 12 14 , 16 , 27 ). A study in China showed that 8.86% of CVD deaths were caused by low temperatures, and 0.17% were caused by high temperatures ( 16 ).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies had generally found that the death burden caused by low temperatures was higher than that of high temperatures ( 12 14 , 16 , 27 ). A study in China showed that 8.86% of CVD deaths were caused by low temperatures, and 0.17% were caused by high temperatures ( 16 ).…”
Section: Discussionmentioning
confidence: 92%
“…Our study found that most of mortality burden attributable to non-optimal temperatures was driven by low temperatures, which is consistent with previous studies. 2 , 5 , 6 , 8 , 18 , 19 Chen et al. reported in a study including 272 main Chinese cities that the PAFs attributable to low and high temperatures were 11·62% and 2·71%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Daily mass concentrations of air pollutants were collected from the China National Environmental Monitoring Centre, and a land-use-regression model was used to obtain more accurate daily PM 2.5 , SO 2 , and O 3 at each location of Guangdong Province, which was similar to Liu's study [25]. Based on the residential districts/counties of each participant, the daily mass concentrations of air pollutants were extracted.…”
Section: Meteorological Data and Air Pollution Datamentioning
confidence: 99%